PENGARUH PROGRAM PEMANTAUAN ELEKTROKARDIOGRAM TERHADAP DETEKSI DINI PENYAKIT JANTUNG - Farras, Reyhan Muhammad; Horman Latuconsina (Jurnal Kesehatan Madani Medika, 2025)
Heart disease is one of the diseases that often goes undetected early on, which can lead to serious complications and death. This study aims to investigate the effect of an electrocardiogram (ECG) monitoring program on the early detection of heart disease. The research method used is quantitative with data collection using questionnaires and regression analysis. The respondents in this study were individuals who had participated in the ECG monitoring program for a certain period. Data were collected through questionnaires that included demographic information, medical history, and participation in the monitoring program. Regression analysis was used to determine the relationship between the independent variable (participation in the ECG monitoring program) and the dependent variable (early detection of heart disease). The results of the study show that there is a significant influence between participation in the ECG monitoring program and early detection of heart disease. The ECG monitoring program has an influence of 61.3% on the early detection of heart disease. The results of this study are expected to contribute to a further understanding of the effectiveness of EKG monitoring programs in the early detection of heart disease. The practical implications of this study may include recommendations to improve accessibility and participation in EKG monitoring programs, as well as more effective heart disease prevention efforts.